Thermal mixing of two miscible fluids in a T-shaped microchannel - Xu, Bin (2012)
In this paper, thermal mixing characteristics of two miscible fluids in a T-shaped microchannel are investigated theoretically, experimentally, and numerically. Thermal mixing processes in a T-shaped microchannel are divided into two zones, consisting of a T-junction and a mixing channel. An analytical two-dimensional model was first built to describe the heat transfer processes in the mixing channel. In the experiments, de-ionized water was employed as the working fluid. Laser induced fluorescence method was used to measure the fluid temperature field in the microchannel. Different combinations of flow rate ratios were studied to investigate the thermal mixing characteristics in the microchannel. At the T-junction, thermal diffusion is found to be dominant in this area due to the striation in the temperature contours. In the mixing channel, heat transfer processes are found to be controlled by thermal diffusion and convection. Measured temperature profiles at the T-junction and mixing channel are compared with analytical model and numerical simulation, respectively.